Pelatihan Dan Pendampingan Optimasi Fotografi Produk Serta Desain Branding Yang Memanfaatkan Teknologi Smartphone Bagi Umkm RW.01, Kedung Baruk, Rungkut, Surabaya - Nugroho, Novianto Eko; Pontjo Bambang Mahargiono; Dian Arini; Ikhsan Budi Riharjo; Djawoto (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2025)
This Community Service Program aims to enhance the skills of SMEs in RW.01, Kelurahan Kedung Baruk, Rungkut District, Surabaya, in utilizing smartphone technology for product photography and branding design. Many SMEs have yet to fully optimize digital technology, especially in creating attractive product visuals and strong branding designs. This training provides practical knowledge on product photography techniques using smartphones, including lighting, angle selection, and basic editing, as well as consistent and appealing branding design. The implementation method involves direct training, mentoring, and evaluation to ensure understanding and application of the material. Initial results show that most participants were able to produce higher-quality product photos and more professional branding designs. Additionally, participants began applying digital marketing strategies through social media platforms such as Instagram and WhatsApp to promote their products. This program is expected to enhance the competitiveness of SMEs, expand their market reach, and provide a positive impact on the sustainability of their businesses and the local economy.